Policy Diffusion by means of Defense and Security Simulations and the uses of agent-based modelling (Revista da EGN, 2023)
This paper is about three elements: inter-agencycooperation simulations with security and defensepractitioners as actors; policy diffusion as a way ofinnovative and incremental gains using practices and theobservation of behaviors; and, agent-based modelling asa tool to enhance performance, observing tendencies andacquiring more visibility of the processes and practicesimbibed. For this, the first part of the paper is focusedon the uses of the literature that expresses decisionmaking process behaviors as a fundamental part of theinstitutionalization process in terms of cooperation.Adaptive institutionalization is the core element of thisapproach; in which we believe policy diffusion can deriveprogressively and in an incremental way. Secondly, weare going to present the inter-agency simulation cases weare working with as part of an inter-institutional effort;researching on those ties and proposing new forms ofarrangements and possibilities of increasing dynamicsefficiency in the sector, observing both the cases and theexercises chosen in agent-based modelling (ABM).